Effect of warming on the carbon flux of the alpine wetland on the Qinghai–Tibet Plateau - Yasin, Adile; Niu, Bin; Chen, Zhengan; Hu, Yilun; Yang, Xiaoqin; Li, Yue; Zhang, Gengxin; Li, Fengjie; Hou, Weiguo (Frontiers in Earth Science, 2022)
Under the scenario of global warming, the response of greenhouse gas emissions from alpine wetlands remains unclear. In this study, fluxes of CO2 and CH4 were measured in daytime for the microtopographic features of hollows and hummocks in a wetland on the Tibetan Plateau under two elevated temperatures, increments of ~1 °C (T1 treatment) and ~2 °C (T2 treatment), during the growing season in 2019. The results show that warming significantly increased cumulative net ecosystem CO2 exchanges (NEE) for both microtopographic features in the wetland compared to the control due to a combination of increased gross primary production (GPP) with a stronger increase in ecosystem respiration (ER). Similarly, warming also increased cumulative CH4 emission significantly. The effect was stronger for T2 compared to T1 for all component fluxes (GPP, ER, NEE, and CH4). Generally, NEE and CH4 fluxes both rose at first and then decreased. NEE peaked at the end of July for both hollows and hummocks, while CH4 emissions peaked in the middle of August. The cumulative CH4 emissions from hummocks were significantly higher than those of hollows, and CH4 emissions under illumination were significantly higher than those in darkness, which may be caused by irradiation-sensitive vegetable internal convective gas transport system which diffuse CH4 from pedosphere. This study revealed that warming strengthened the function of CO2 sink but also increased CH4 emissions from the alpine wetlands on the Qinghai-Tibet Plateau.